2015
DOI: 10.3109/00365521.2015.1065510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immunohistochemical markers according to histological type in patients with early gastric cancer

Abstract: IHC analysis showed that EGC histological types differ in terms of mucin phenotype and biological characteristics. The poorly cohesive components showed decreased E-cadherin and β-catenin expression levels and increased vascular endothelial growth factor expression. These characteristics may contribute to the poor prognosis of patients with MAC and PCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
0
6
0
1
Order By: Relevance
“…In the present study, two patients with poor differentiation showed loss of E-cadherin expression, but it was difficult to perform statistical analysis owing to the small number of cases. According to a recent report, loss of E-cadherin expression and overexpression of VEGF are more common with poor histological differentiation in patients with EGC [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, two patients with poor differentiation showed loss of E-cadherin expression, but it was difficult to perform statistical analysis owing to the small number of cases. According to a recent report, loss of E-cadherin expression and overexpression of VEGF are more common with poor histological differentiation in patients with EGC [15].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported that GC that had both intestinal and diffuse types had a significantly higher enhanced CpG island hypermethylation status associated with tumor suppressive genes. More recently, Han et al demonstrated that the poorly cohesive components of mixed adenocarcinoma showed decreased E‐cadherin and β‐catenin expression levels and increased vascular endothelial growth factor expression. They discussed that the results indicated these characteristics might contribute to the poor prognosis of patients with mixed adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the combinations of expression of these markers, the 257 EGCs were classified into the G-type (21 %, 54/257), GI-type (56 %, 144/257), I-type (20 %, 51/ 257) and N-type (3 %, 8/257); in previous reports, the incidence percentages of each of these mucin phenotypes were found to be 15-41.1 %, 20.3-60.1 %, 18.5-46.6 %, and 3.7-31.6 %, respectively, in advanced GCs [3,13,14], and 7.9-36.8 %, 18.8-41.2 %, 15.4-55.56 %, and 0-11.1 %, respectively, in early-stage GCs [7,11,[19][20][21][22][23][24][25]. Our results were consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%